Smart Machines : IBM's Watson and the Era of Cognitive Computing. - Kelly III, John E. (Columbia Business School publishing., 2013)
We are entering a new frontier in the evolution of computing: the era of cognitive systems. The victory of IBM's Watson on the television quiz show Jeopardy! signaled the advent of this new era, revealing how scientists and engineers at IBM and elsewhere are pushing the boundaries of science and technology to create machines that sense, learn, reason, and interact with people in new ways. In Smart Machines, John E. Kelly III, director of IBM Research, and Steve Hamm, a writer at IBM and a former business and technology journalist, introduce the fascinating world of?cognitive syste.